2017
DOI: 10.1007/s00127-017-1445-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the structure and meaningfulness of the dissociative subtype of PTSD

Abstract: PurposeStudies conducted in the USA, Canada and Denmark have supported the existence of the dissociative PTSD subtype, characterized primarily by symptoms of depersonalization and derealization. The current study aimed to examine the dissociative PTSD subtype in an Eastern European, predominantly female (83.16%) sample, using an extended set of dissociative symptoms.MethodsA latent profile analysis was applied to the PTSD and dissociation data from 689 trauma-exposed university students from Slovakia.ResultsFo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Finally, in the GPS, dissociative symptoms load on a separate factor, coherently with the DSM 5 dissociative specification (Hansen et al, 2017b;Longo et al, 2019;Rossi et al, 2019). The fact that dissociation loads onto a separate factor supports the Subtype model of the relationship between PTSD and dissociation (Hansen et al, 2017b;Ross et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…Finally, in the GPS, dissociative symptoms load on a separate factor, coherently with the DSM 5 dissociative specification (Hansen et al, 2017b;Longo et al, 2019;Rossi et al, 2019). The fact that dissociation loads onto a separate factor supports the Subtype model of the relationship between PTSD and dissociation (Hansen et al, 2017b;Ross et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…PTSD than trauma-exposed individuals without PTSD (Megías, Ryan, Vaquero, & Frese, 2007;Porter & Birt, 2001). Instead, it has been suggested that this symptom might be a defining feature of the dissociative subtype of PTSD (Miller et al, 2013;Ross, Baník, Dědová, Mikulášková, & Armour, 2018), as memory impairments have long been considered to be a symptom of dissociation (Dorahy & van der Haart, 2015;Lanius, Brand, Vermetten, Frewen, & Spiegel, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This factor partially overlaps with DSM 5 criterion D 'Negative alterations in mood and cognition' as well as with the 'disturbances in selforganization' (DSO) criteria that characterize complex-PTSD in ICD-11 (Cloitre et al, 2013;Karatzias et al, 2017;Shevlin et al, 2018). Finally, in the GPS, dissociative symptoms constitute a separate factor, coherently with the DSM-5 dissociative specification of PTSD ('PTSD with dissociative symptoms') (Hansen, Ross, & Armour, 2017b;Longo, Cecora, Rossi, Niolu, & Siracusano, 2019;Rossi et al, 2019) and with the Dissociative Subtype model of PTSD (Hansen et al, 2017b;Ross, Baník, Dědová, Mikulášková, & Armour, 2018). The inclusion of cognitive and affective symptoms in the PTSD criteria by DSM 5 has produced a large number of different hypothesized latent factor structures of PTSD, with the result of increased confusion in stress-related disorders taxonomy (Hansen, Hyland, Armour, Shevlin, & Elklit, 2015).…”
Section: Discussionmentioning
confidence: 99%